Pre-/Post-Harvest Pathogen-Control Strategies for Improving the Quality and Safety of Horticultural Plants - Tae Jin Cho (Horticulturae, 2023)
The microbiological safety of horticultural plants (vegetables, fruits, spices, flowers, other edible crops, ornamental plants, etc [...]